A Clinico-Hematological Profile of Dengue Outbreak Among Healthcare Professionals in A Tertiary Care Hospital of Ahmedabad with Analysis on Economic Impact - Abhinav Jain; Asha N Shah; Pinakin Patel; Mitali Desai; Shrikant Somani; Pallav Parikh; Roopesh Singhal; Dinesh Joshi (National Journal of Community Medicine, 2013)
Introduction: There has been a recent surge of Dengue infections in India, with many outbreaks in urban areas. This study is the biggest documented in-hospital dengue fever outbreak among health care personnel in India.